A multidisciplinary team and patient perspective on omission of surgery after neoadjuvant systemic therapy for early breast cancer: a European Society of Surgical Oncology (ESSO) research academy survey - Caballero, Carmela; Lundon, Dara J.; Vasileva-Slaveva, Mariela; Montagna, Giacomo; Bonci, Eduard-Alexandru; Brandl, Andreas; Smith, Henry; Kok, Johnn Henry Herrera; Holmberg, Carl-Jacob; Sayyed, Raza; Santrac, Nada; Suppan, Ina; et al. (European journal of surgical oncology, 2024)
Background - Surgical de-escalation aims to reduce morbidity without compromising oncological outcomes. Trials to de-escalate breast cancer (BC) surgery among exceptional responders after neoadjuvant systemic therapy (NST) are ongoing. Combined patient and clinician insights on this strategy are unknown. - Methods - The European Society of Surgical Oncology Young Surgeons Alumni Club (EYSAC) performed an online survey to evaluate the perspective of multidisciplinary teams (MDTs) on omission of surgery (“no surgery”) following complete response to NST for early BC. The aim was to identify MDT considerations and perceived barriers to omission of BC surgery. Patient insights were obtained through a focused group discussion (FGD) with four members of the patient advocacy group, Guiding Researchers and Advocates to Scientific Partnerships (GRASP). - Results - The MDT survey had 248 responses, with 229 included for analysis. Criteria for a “no surgery” approach included: patient's tumor and nodal status before (39.7 %) and after (45.9 %) NST and comorbidities (44.3 %). The majority chose standard surgery for hypothetical cases with a complete response to NST. Barriers for implementation were lack of definitive trials (55.9 %), “no surgery” not being discussed in MDTs (28.8 %) and lack of essential diagnostic or therapeutic options (24 %). Patients expressed communication gaps about BC surgery, lack of trust regarding accuracy of imaging, fear of regret and psychosocial burden of choosing less extensive surgery. - Conclusions - Before accepting “no surgery” after complete response to NST, MDTs and patients need level 1 evidence from clinical trials, access to standard diagnostic modalities and treatments. Patient's fear of regretting less surgery need to be acknowledged and addressed.
Online verfügbar: 14. August 2024
Gesehen am 12.11.2024